2005
DOI: 10.1189/jlb.0205091
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide3-kinase regulates actin polymerization during delayed phagocytosis ofHelicobacter pylori

Abstract: We have shown previously that ulcerogenic (type I) strains of Helicobacter pylori (Hp) retard their entry into macrophages. However, the signaling pathways that regulate Hp phagocytosis are largely undefined. We show here that Hp strongly activated class IA phosphoinositide3-kinases (PI3Ks) in macrophages, coincident with phagocytosis, and endogenous p85 and active protein kinase Bα accumulated on forming phagosomes. PI3K inhibitors, wortmannin and LY294002, inhibited phagocytosis of Hp in a dose-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
41
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 68 publications
5
41
1
Order By: Relevance
“…Our results have shown that selective inhibition of p38 activation by a specific inhibitor, or by knocking down p38 expression using siRNAs, reduced LPS-induced phagocytosis of E. coli, suggesting that LPS also regulates phagocytosis of E. coli partially through the MyD88-p38 signaling pathway. PI3K has been shown to provide a critical signal for cell phagocytosis [28,29]. However, in our experiments, phagocytosis of E. coli cannot be blocked by either the PI3K specific inhibitor LY294002 or wortmannin (data not shown).…”
Section: Discussioncontrasting
confidence: 51%
“…Our results have shown that selective inhibition of p38 activation by a specific inhibitor, or by knocking down p38 expression using siRNAs, reduced LPS-induced phagocytosis of E. coli, suggesting that LPS also regulates phagocytosis of E. coli partially through the MyD88-p38 signaling pathway. PI3K has been shown to provide a critical signal for cell phagocytosis [28,29]. However, in our experiments, phagocytosis of E. coli cannot be blocked by either the PI3K specific inhibitor LY294002 or wortmannin (data not shown).…”
Section: Discussioncontrasting
confidence: 51%
“…PI3K activity effects changes in the cytoskeleton and affects actin polymerization, which is a key element in uptake of bacteria into host cells (41,44). It has also been shown to play a role in Francisella entry (this study and Refs.…”
Section: Discussionmentioning
confidence: 97%
“…PI3K plays a role for the entry process of many bacteria (e.g., (41)(42)(43)(44) and viruses (45). PI3K activity effects changes in the cytoskeleton and affects actin polymerization, which is a key element in uptake of bacteria into host cells (41,44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that SHIP-1 is present on phagosomal membranes early but redistributes back to the cytosol after phagosomal closure (37,56). These early SHIP-1 activities may bias subsequent phagosome formation and maturation.…”
Section: Discussionmentioning
confidence: 99%